RECENT GEODYNAMICS OF FAULT ZONES: FAULTING IN REAL TIME SCALE - Yu. O. Kuzmin (Геодинамика и тектонофизика)
Recent deformation processes taking place in real time are analyzed on the basis of data on fault zones which were collected by long-term detailed geodetic survey studies with application of field methods and satellite monitoring.A new category of recent crustal movements is described and termed as parametrically induced tectonic strain in fault zones. It is shown that in the fault zones located in seismically active and aseismic regions, super intensive displacements of the crust (5 to 7 cm per year, i.e. (5 to 7)·10–5 per year) occur due to very small external impacts of natural or technogenic / industrial origin.The spatial discreteness of anomalous deformation processes is established along the strike of the regional Rechitsky fault in the Pripyat basin. It is concluded that recent anomalous activity of the fault zones needs to be taken into account in defining regional regularities of geodynamic processes on the basis of real-time measurements.The paper presents results of analyses of data collected by long-term (20 to 50 years) geodetic surveys in highly seismically active regions of Kopetdag, Kamchatka and California. It is evidenced by instrumental geodetic measurements of recent vertical and horizontal displacements in fault zones that deformations are ‘paradoxically’ deviating from the inherited movements of the past geological periods.In terms of the recent geodynamics, the ‘paradoxes’ of high and low strain velocities are related to a reliable empirical fact of the presence of extremely high local velocities of deformations in the fault zones (about 10–5 per year and above), which take place at the background of slow regional deformations which velocities are lower by the order of 2 to 3. Very low average annual velocities of horizontal deformation are recorded in the seismic regions of Kopetdag and Kamchatka and in the San Andreas fault zone; they amount to only 3 to 5 amplitudes of the earth tidal deformations per year.A ‘fault-block’ dilemma is stated for the recent geodynamics of faults in view of interpretations of monitoring results. The matter is that either a block is an active element generating anomalous recent deformation and a fault is a ‘passive’ element, or a fault zone itself is a source of anomalous displacements and blocks are passive elements, i.e. host medium. ‘Paradoxes’ of high and low strain velocities are explainable under the concept that the anomalous recent geodynamics is caused by parametric excitation of deformation processes in fault zones in conditions of a quasi-static regime of loading.Based on empirical data, it is revealed that recent deformation processes migrate in fault zones both in space and time. Two types of waves, ‘inter-fault’ and ‘intra-fault’, are described. A phenomenological model of auto-wave deformation processes is proposed; the model is consistent with monitoring data. A definition of ‘pseudo-wave’ is introduced. Arrangements to establish a system for monitoring deformation auto-waves are described.When applied to geological deformation monitoring, new measurement technologies are associated with result identification problems, including ‘ratios of uncertainty’ such as ‘anomaly’s dimensions – density of monitoring stations’ and ‘anomaly’s duration – details of measurements in time’. It is shown that the RSA interferometry method does not provide for an unambiguous determination of ground surface displacement vectors.